Evaluation of TRMM satellite rainfall estimates (algorithms 3B42 V7 and RT) over the Santo Antônio county (Goiás, Brazil) (2017)
The rainfall has a direct influence on the agricultural productivity, being indispensable the knowledge of its spatiotemporal behavior in order to establish trends that will assist in the management of water resources, agricultural planning, hydrological monitoring and prevention of natural disasters. Thus, this work aimed to evaluate the accuracy of the TRMM satellite precipitation estimates in relation to the recorded precipitation. For this, the rainfall data from the weather station located in the municipality of Santo Antônio de Goiás - GO were used, being compared to the data of the TRMM satellite, algorithms 3B42 Version 7 and Real Time, in the period from January 1998 to October 2015. The comparison of the TRMM satellite data showed that the ten-day and monthly precipitation records of the algorithm 3B42 V_7 showed correlation values of 0.69 and 0.65, respectively, in the rainy season; in the dry season, the correlations were of 0.80 and 0.73. The ten-day concordance index ranged from 0.68 to 0.98 and the monthly concordance index ranged from 0.83 to 0.99. The algorithm 3B42 Real Time presented lower statistical results when compared to the 3B42 V_7. The satellite precipitation estimates showed both trends of overestimation and underestimation; however, the satellite data can help research in the absence of information on the rainfall in the region.